Electron transfer mechanism of graphene/Cu heterostructure for improving the stability of triboelectric nanogenerators. (April 2020) - Li, Yahui; Zheng, Wei; Zhang, Haodong; Wang, Haoqiang; Cai, Han; Zhang, Yanxin; Yang, Zhuoqing
Abstract: Harvesting energy from the mechanical motion has been demonstrated to be a preferable strategy to satisfy the requirements for self-powered electronics. Here we report a flexible and stable induction electrode based on graphene/Cu heterostructure, which is fabricated by electrodeposition and spin-coating, and is also utilized in energy harvesting for triboelectric nanogenerator (TENG). Typically, graphene dispersion prepared by physical exfoliation is spin-coated on the copper nanostructure based on PDMS. Besides, we provide favorable evidences that electrons transfer from graphene to copper, and ignite the reduced reaction of copper oxides. The function of graphene in avoiding the oxidation of copper nanostructure, thus improving the stability of graphene/Cu heterostructure and achieving its applications in triboelectric nanogenerator, is confirmed. The interactive mechanism is formulated, including energy barrier, metal work function and the electrochemical potential difference between graphene, copper and oxygen. The enhanced stability of graphene/Cu heterostructure is inspected by the chemical state of copper as the function of exposure time, and the applicability is also evaluated by their output electrical performance for TENG applications. Graphical abstract: Image 1 Highlights: Electrodeposition is proved to be feasible for fabricating flexible electrode in TENG. Electron transfer mechanism of graphene/Cu heterostructure is proposed and verified. Skin-based flexible S-TENG is utilized for energy harvesting.